Metode KKN-PPM Sebagai Upaya Pemberdayaan Perempuan dalam Produksi dan Pemasaran Ecoprint Era Digital (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
The Community Empowerment Real Work Lecture Program (KKN-PPM) is a research-based service activity that involves students to assist the community in developing local potential. This article discusses the KKN-PPM method as an effort to empower women through the production and marketing of ecoprints in the digital era. Ecoprint was chosen because it is an environmentally friendly craft with high artistic and economic value, but its development is still constrained by limited production skills and marketing access. This research uses a participatory approach through the stages of observation, planning, implementation of digital production and marketing training, monitoring-evaluation, and program sustainability planning. The results of the activity showed that there was an increase in women's skills in ecoprint techniques  (hammering, steaming, boiling), design quality, and product diversification into hijabs, bags, pillowcases, and others. From the marketing aspect, participants managed to utilize social media and marketplaces (Shopee, Tokopedia) to expand the market reach to outside the region. This program also fosters confidence, entrepreneurial spirit, and the formation of more independent women's business groups. Thus, the application of the KKN-PPM method has proven to be effective as a strategy for women's empowerment that is able to strengthen the family economy while encouraging the independence of creative businesses based on local potential in the digital era.
Keywords: KKN-PPM; Women's Empowerment; Ecoprint; Digital Marketing; Creative Economy; Local Potential